Analyzing the Brand Equity of Prospective Postgraduate Program of Islamic University - Kirana, Dhinuk Puspita; Wulansari, Andhita Dessy (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research focused on the brand equity assets of the Postgraduate of IAIN Ponorogo, precisely the perceived quality and brand association factors that affect consumer decisions. It was related to the choice of the 8th-semester students of IAIN Ponorogo in the academic year 2022/2023 in choosing the Postgraduate program. This research employed a quantitative methodology using binary logistic regression statistical techniques. It also used a random sampling method, randomly choosing student identification numbers to choose the sample. Therefore, every member of the population had an equal chance of being included in the sample, ensuring that the sample was representative of the population for research purposes. Questionnaires were used to gather key information: brand association, perceived quality, and brand awareness. The findings of this research show that: 1) the Postgraduate of IAIN Ponorogo ranked first for the top of mind level, with UIN Yogyakarta occupying the second spot; and 2) the internal quality of the Postgraduate program had a considerable impact on whether or not the 8th-semester students of the IAIN Ponorogo prioritized the Postgraduate program of IAIN Ponorogo.